Pengaruh Waktu Pemberian Pakan Buatan Tehadap Pertumbuhan dan kelangsungan Hidup Ikan Lele (Clarias sp.) - Afnianti Sianturi; Syammaun Usman (AQUACOASTMARINE, 2018)
Catfish is one of the freshwater fish that has developed cultivation in the community because it can be cultivated in limited places and high density and has the advantage, fast growth and resistance to disease. The speed of fish growth rate is strongly influenced by the type, quality and management of feed given and environmental conditions. The study were used Completely Randomized Design (RAL) with 3 treatments and 3 replications, as follows: P1 (Time feeding 3 times daily), P2 (Time feeding 4 times daily) and P3 (Time feeding 5 times daily ). The data were analyzed using Analysis of Variance (ANOVA), followed by the Smallest Significant Difference (BNT) test. The results showed that the frequency treatment of different feeding significantly affected the growth but did not significantly affect the survival of catfish. The best feeding time in increasing the growth and survival of catfish is P3 treatment with larva length increase of 8,0 cm and weight increase 32,24gr.Keywords : Clarias sp., Feeding Time, Growth